Analisis Dampak AI Chatbot Sebagai Media Dukungan Psikologis Terhadap Kesehatan Mental Pengguna - Zulas, Lailatul Maghfirah; M. Fahli Zatrahadi,; Miftahuddin, Miftahuddin (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Advances in artificial intelligence (AI) technology have led to the emergence of AI-based chatbots, which are increasingly being used as a medium for psychological support. This study aims to conduct an in-depth analysis of the impact of AI chatbot use on users’ mental health from the perspective of subjective experience, perception, and meaning constructed by the users themselves. The study employs a qualitative approach using a multiple case study design across three AI chatbot platforms—Woebot, Wysa, and Replika—involving 18 participants selected through purposive sampling. Data were collected via semi-structured in-depth interviews, limited participant observation, and documentation of digital artifacts, and were analyzed using reflexive thematic analysis and cross-case synthesis. The findings indicate that AI chatbots provide positive impacts, including tangible emotional support, improved self-regulation, and accessibility free from social barriers. However, risks of dependency, limitations in managing severe conditions, and concerns about data privacy emerged as significant recurring themes. This study underscores the importance of positioning AI chatbots as a complement within the broader mental health care ecosystem, rather than as a substitute for professionals. Practical implications for developers, practitioners, and policymakers are also outlined.